Impacts of dimethyl phthalate on the bacterial community and functions in black soils - Wang, Zhi-Gang; Hu, Yun-Long; Xu, Wei-Hui; Liu, Shuai; Hu, Ying; Zhang, Ying (Frontiers in Microbiology, 2015)
Dimethyl phthalate (DMP), also known as endocrine disruptor and one of the phthalate esters (PAEs), is ubiquitous environmental pollutant, and the impacts on human health arouse great concerns. In this study, a microcosm model was set up and adopted to test the impacts of DMP contamination on bacterial community and function in black soils. The results showed that the operational taxonomic units (OTUs) richness and diversity of bacteria in black soils were inhibited by DMP contamination. The relative populations of some genera that associated with nitrogen metabolism were increased by DMP contamination; while the relative populations of some other genera that were beneficial extremely to soil health were inhibited by DMP contamination; the relative populations of some genera which had some capability to degrade DMP were increased under lower DMP treatments (5, 10 and 20 mg/kg), but were inhibited under higher DMP treatment (40 mg/kg). Clearly, DMP contamination changed the bacterial community structure, and disturbed the metabolic activity and functional diversity of the microbes and enzymes in black soils. Furthermore, it suggests DMP pollution could alter the metabolism and biodiversity of black soils, and cause direct impacts of fertility and ecosystem function in black soils.